Models for the edition of Gothic texts: the case of the Gotica Carolina - Alessandro Zironi (Filologia Germanica)
The paper takes into consideration the different typologies of critical edition concerning the Gothic Bible. Starting from that survey, the author stresses that many Gothic texts have been edited sometimes without taking into account their different genre and their relationships with Greek and Latin models. Consequently, it is necessary to propose new editorial models for every type of Gothic text. Every edition should actually be planned after having defined the textual typology which the text can more easily be compared with. A good example could be the textual typologies conceived for editing Old High German texts. After having discussed that model, which is certainly useful also for Gothic texts, the author proposes criteria for a new editorial hypothesis of some Gothic texts (Gotica Vindobonensia and Gotica Parisina) in which codicological considerations are core points for the construction of the new edition.